Advances for the treatment of lower extremity arterial disease associated with diabetes mellitus - Pan, Yang; Luo, Yuting; Hong, Jing; He, Huacheng; Dai, Lu; Zhu, Hong; Wu, Jiang (Frontiers in Molecular Biosciences, 2022)
Lower extremity arterial disease (LEAD) is a major vascular complication of diabetes. Vascular endothelial cells dysfunction can exacerbate local ischemia, leading to a significant increase in amputation, disability, and even mortality in patients with diabetes combined with LEAD. Therefore, it is of great clinical importance to explore proper and effective treatments. Conventional treatments of diabetic LEAD include medication based on health management, endovascular revascularization and surgery. As interdisciplinary research emerges, regenerative medicine strategies have provided new insights to treat critical limb ischemia (CLI). Therapeutic angiogenesis strategies, such as delivering growth factors, stem cells, drugs to ischemic tissues, have also been proposed to treat LEAD by fundamentally stimulating multidimensional vascular regeneration. Recent years have seen the rapid growth of tissue engineering technology; tissue-engineered biomaterials have been used to study the treatment of LEAD, such as encapsulation of growth factors and drugs in hydrogel to facilitate the restoration of blood perfusion in ischemic tissues of animals. The primary purpose of this review is to introduce treatments and novel biomaterials development in LEAD. Firstly, the pathogenesis of LEAD is briefly described. Secondly, conventional therapies and therapeutic angiogenesis strategies of LEAD are discussed. Finally, recent research advances and future perspectives on biomaterials in LEAD are proposed.